Superfine cement grinding aid composition and preparation method thereof
An ultrafine cement grinding aid was prepared by using a terpolymer with a specific structure (MAEA/AMPS/AM). This solved the problems of high energy consumption, poor particle dispersibility, and difficulty in achieving both early strength and long-term performance in the ultrafine cement grinding process. It achieved efficient grinding and early strength improvement and is suitable for the production of cement with high specific surface area.
Patent Information
- Application Number
- CN202511193385.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-25
- Publication Date
- 2025-11-28
AI Technical Summary
In the process of ultrafine cement grinding, energy consumption is high, particle dispersion is poor, and it is difficult to balance early strength and long-term performance. Existing grinding aids have shortcomings.
Ultrafine cement grinding aids were prepared by free radical copolymerization using a terpolymer with a specific structure (MAEA/AMPS/AM). By combining molecular weight control and compounding technology, an oxidation-reduction initiation system and chain transfer agent were used in the preparation process to form stable coordination bonds, electrostatic repulsion and physical barriers, which synergistically reduced energy consumption and improved strength.
It significantly reduces grinding energy consumption by 32%–38%, increases 3-day compressive strength by 28%–35%, ensures particle dispersibility and early hydration reaction, and is suitable for the production of ultrafine cement with a specific surface area ≥550m²/kg.
Smart Images

Figure BDA0005564400660000101
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of cement additives, and particularly relates to a superfine cement grinding aid composition and a preparation method thereof. BACKGROUND
[0002] In the cement production process, grinding is one of the links with the highest energy consumption, accounting for about 60-70% of the total power consumption of cement production. With the development of the cement industry towards high grade and high performance, the demand for superfine cement (specific surface area > 500 m 2 / kg) is increasing. However, there are the following technical problems in the superfine cement grinding process:
[0003] High grinding energy consumption: the high specific surface area of superfine particles leads to a sharp increase in surface energy, and the particles are easy to agglomerate, so more mechanical energy is needed to overcome the surface adsorption force during grinding, resulting in a substantial increase in power consumption; poor particle dispersion: traditional grinding aids (such as triethanolamine and lignosulfonate) have insufficient electrostatic stabilization effect on small particles, and the particle size distribution after grinding is wide, which easily forms "secondary agglomeration", affecting the fluidity and strength development of cement; it is difficult to balance early strength and long-term performance: some grinding aids can reduce grinding energy consumption, but they interfere with the cement hydration process, resulting in low early strength or slow long-term strength growth, affecting engineering applications.
[0004] At present, commercially available grinding aids are mainly divided into two categories: small molecule grinding aids (such as triethanolamine and ethylene glycol): strong adsorption, but easy to desorb, and cannot provide long-term steric hindrance, so the effect on superfine cement is limited. High molecular weight grinding aids (such as polycarboxylic acid): good dispersion, but when the molecular weight is too high, it can easily cause the viscosity of the slurry to rise, and may delay the setting of the cement.
[0005] In recent years, researchers have tried to optimize the performance of grinding aids through copolymer design. For example: CN108409907A discloses an acrylic acid / 2-acrylamide-2-methylpropanesulfonic acid copolymer grinding aid, but it lacks a catalytic group for cement hydration, and the early strength improvement is not obvious. Therefore, the development of a multifunctional grinding aid with efficient grinding, stable dispersion of particles, and strength enhancement has become an urgent need in the production of superfine cement. The present application effectively solves the above problems by designing a specific structure of terpolymer (MAEA / AMPS / AM), combining molecular weight regulation and compounding technology. SUMMARY
[0006] Therefore, the present application aims to provide a superfine cement grinding aid composition and a preparation method thereof.
[0007] A terpolymer for a superfine cement grinding aid is prepared by free radical copolymerization of maleic acid ethanolamine ester (MAEA), 2-acrylamide-2-methylpropane sulfonic acid (AMPS) and acrylamide (AM), the molar ratio of the monomers being MAEA:AMPS:AM=1:(0.3-0.6):(1.2-2.5), and the weight average molecular weight of the terpolymer being 200,000-350,000.
[0008] The preparation method of the terpolymer comprises the following steps:
[0009] (1) dissolving MAEA, AMPS and AM in water to prepare an aqueous solution with a total monomer concentration of 22-28%;
[0010] (2) adding an oxidation-reduction initiation system comprising ammonium persulfate and vitamin C, wherein the addition amount of ammonium persulfate is 0.4-0.7% of the total mass of the monomers, the addition amount of vitamin C is 0.3-0.4% of the total mass of the monomers, and a chain transfer agent is added;
[0011] (3) reacting at 62-68°C for 4.5-5.5 hours under nitrogen protection, and then precipitating and drying the product to obtain the terpolymer.
[0012] Preferably, the pH of the aqueous solution of (1) is controlled to be 6.2-6.8.
[0013] Preferably, the chain transfer agent of (2) is dodecyl mercaptan or mercaptoacetic acid, and the addition amount is 0.2-0.4% of the total mass of the monomers.
[0014] Preferably, the terpolymer accounts for 25-45% of the total mass of the superfine cement grinding aid composition, water accounts for 45-55% of the total mass of the superfine cement grinding aid composition, and the grinding aid enhancer accounts for 7-13% of the total mass of the superfine cement grinding aid composition, and the grinding aid enhancer is at least one selected from triisopropanolamine, diethanol monoisopropanolamine and sodium gluconate.
[0015] Preferably, the superfine cement grinding aid composition further comprises 1-1.5% of a retarder, and the retarder is boric acid, citric acid or tartaric acid.
[0016] Preferably, the superfine cement grinding aid composition comprises the following steps in application: dissolving the terpolymer in water and stirring until completely dissolved; adding the grinding aid enhancer and the retarder in sequence, and stirring and mixing at 28-35°C for 0.6-0.8 hours to obtain a homogeneous solution.
[0017] Preferably, the amount of the ultrafine cement grinding aid composition added is 0.03% to 0.07% of the cement mass.
[0018] Preferably, the cement has a specific surface area ≥ 550 m². 2 / kg of ultrafine cement.
[0019] Preferably, the ultrafine cement grinding aid composition can reduce grinding energy consumption by 32% to 38% and increase 3-day compressive strength by 28% to 35%.
[0020] The beneficial effects of this invention are:
[0021] 1. This invention reduces energy consumption by 32%–38% during cement grinding through the synergistic effect of a specific ratio of terpolymers (MAEA / AMPS / AM). This effect stems from the following technical mechanism: the ethanolamine groups (-N(CH3CH2OH)) of maleic acid ethanolamine ester (MAEA) can react with the Ca2+ on the surface of cement particles. 2 +、Al 3 The formation of stable coordination bonds by metal ions effectively reduces the surface energy of particles, allowing mechanical energy to act more efficiently on particle crushing rather than being consumed by surface energy during the grinding process; the sulfonic acid group (-SOH) of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) ionizes into -SO3 in aqueous solution. - It imparts a strong negative charge to the surface of cement particles, preventing particle agglomeration through electrostatic repulsion and reducing the "secondary grinding" phenomenon during the grinding process; the nonionic properties of acrylamide (AM) bind to cement particles through hydrogen bonds, and its flexible long-chain structure forms a physical barrier on the particle surface, further preventing particle contact and agglomeration.
[0022] 2. The grinding aid composition of the present invention can increase the 3-day compressive strength of cement by 28% to 35% without affecting the long-term strength development after 28 days. Its technical advantage lies in the interaction between the ethanolamine groups of MAEA and the Ca produced by the hydration of tricalcium silicate (CS) in cement. 2 The addition of this grinding aid forms soluble complexes, accelerates CS dissolution, and promotes early nucleation and growth of the hydration product CSH gel. Cement incorporating this grinding aid experiences an earlier 3-hour hydration exothermic peak by 40 minutes, and a 25% increase in CSH gel formation after 3 days. Simultaneously, the dispersion effect of AMPS results in a more uniform distribution of cement particles and a shift in pore size towards smaller pores, significantly improving density. By compounding with 1%–1.5% retarders (such as citric acid), the ethanolamine group's accelerating effect is neutralized, controlling the initial setting time to 2–3 hours (standard requirement ≥45 minutes), thus preventing a decline in workability.
[0023] 3. The grinding aid composition of this invention solves the technical problem of easy agglomeration and poor flowability of high specific surface area particles: by using a chain transfer agent (dodecyl mercaptan) to control the weight-average molecular weight of the copolymer to 200,000-350,000, it ensures that the polymer chain length can be fully adsorbed on the particle surface without causing an increase in system viscosity due to excessively high molecular weight. The grinding aid reinforcing agent (such as triisopropanolamine) works synergistically with the terpolymer to further reduce the powder friction coefficient. When the addition amount of this composition is 0.03%-0.07% of the cement mass, it can significantly reduce grinding energy consumption by 32%-38% and increase 3-day compressive strength by 28%-35%, and is particularly suitable for specific surface areas ≥550m². 2 Production of ultrafine cement per kilogram. Detailed Implementation
[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0025] Example 1:
[0026] (1) Monomer preparation: Dissolve MAEA, AMPS and AM in water at a molar ratio of 1:0.4:1.5 to prepare an aqueous solution with a total monomer concentration of 25% and control the pH of the reaction system to 6.5.
[0027] (2) Initiation system addition: Add ammonium persulfate at a rate of 0.5% of the total monomer mass, add vitamin C at a rate of 0.35% of the total monomer mass, and add dodecyl mercaptan at a rate of 0.3% of the total monomer mass.
[0028] (3) Reaction process: Under nitrogen protection, the reaction was carried out at 65°C for 5 hours. After the reaction was completed, the terpolymer was obtained by ethanol precipitation and drying.
[0029] (4) Preparation of grinding aid composition: Dissolve the obtained terpolymer in water at a ratio of 30% of the total mass of the ultrafine cement grinding aid composition, add the grinding aid reinforcing agent triisopropanolamine at a ratio of 10% of the total mass of the ultrafine cement grinding aid composition, add the retarder boric acid at a ratio of 1.2% of the total mass of the ultrafine cement grinding aid composition, stir and mix at 30°C for 0.7 hours to obtain the ultrafine cement grinding aid composition.
[0030] Example 2
[0031] (1) Monomer preparation: Dissolve MAEA, AMPS and AM in water at a molar ratio of 1:0.5:2 to prepare an aqueous solution with a total monomer concentration of 28% and control the pH of the reaction system to 6.8.
[0032] (2) Initiation system addition: Add ammonium persulfate at a rate of 0.6% of the total monomer mass, add vitamin C at a rate of 0.4% of the total monomer mass, and add mercaptoacetic acid at a rate of 0.4% of the total monomer mass.
[0033] (3) Reaction process: Under nitrogen protection, the reaction was carried out at 68°C for 5.5 hours. After the reaction was completed, the terpolymer was obtained by ethanol precipitation and drying.
[0034] (4) Preparation of grinding aid composition: Dissolve the obtained terpolymer in water at a ratio of 40% of the total mass of the ultrafine cement grinding aid composition, add the grinding aid reinforcing agent diethanol monoisopropanolamine at a ratio of 12% of the total mass of the ultrafine cement grinding aid composition, add the retarder citric acid at a ratio of 1.5% of the total mass of the ultrafine cement grinding aid composition, stir and mix at 35°C for 0.8 hours to obtain the ultrafine cement grinding aid composition.
[0035] Example 3
[0036] (1) Monomer preparation: Dissolve MAEA, AMPS and AM in water at a molar ratio of 1:0.3:1.2 to prepare an aqueous solution with a total monomer concentration of 22% and control the pH of the reaction system to 6.2.
[0037] (2) Initiation system addition: Add ammonium persulfate at a rate of 0.4% of the total monomer mass, add vitamin C at a rate of 0.3% of the total monomer mass, and add dodecyl mercaptan at a rate of 0.2% of the total monomer mass.
[0038] (3) Reaction process: Under nitrogen protection, the reaction was carried out at 62°C for 4.5 hours. After the reaction was completed, the terpolymer was obtained by ethanol precipitation and drying.
[0039] (4) Preparation of grinding aid composition: Dissolve the obtained terpolymer in water at a ratio of 25% of the total mass of the ultrafine cement grinding aid composition, add grinding aid reinforcing agent sodium gluconate at a ratio of 7% of the total mass of the ultrafine cement grinding aid composition, add retarder boric acid at a ratio of 1.0% of the total mass of the ultrafine cement grinding aid composition, stir and mix at 28°C for 0.6 hours to obtain the ultrafine cement grinding aid composition.
[0040] Comparative Example 1 (Triethanolamine)
[0041] The difference between Comparative Example 1 and Example 1 is that the traditional grinding aid triethanolamine is used to replace the terpolymer, accounting for 30% of the total mass of the ultrafine cement grinding aid composition, while the remaining components are added in the same way as in Example 1.
[0042] Comparative Example 2 (without chain transfer agent)
[0043] (1) Monomer preparation: Dissolve MAEA, AMPS and AM in water at a molar ratio of 1:0.4:1.5 to prepare an aqueous solution with a total monomer concentration of 25% and control the pH of the reaction system to 6.5.
[0044] (2) Initiation system addition: Ammonium persulfate was added at a rate of 0.5% of the total monomer mass, vitamin C was added at a rate of 0.35% of the total monomer mass, and no chain transfer agent was added.
[0045] (3) Reaction process: Under nitrogen protection, the reaction was carried out at 65°C for 5 hours. After the reaction was completed, the terpolymer was obtained by ethanol precipitation and drying.
[0046] (4) Preparation of grinding aid composition: Dissolve the obtained terpolymer in water at a ratio of 30% of the total mass of the composition, add the grinding aid reinforcing agent triisopropanolamine at a ratio of 10% of the total mass of the composition, add the retarder boric acid at a ratio of 1.2% of the total mass of the composition, stir and mix at 30°C for 0.7 hours to obtain the ultrafine cement grinding aid composition.
[0047] Comparative Example 3 (MAEA / AM binary copolymer)
[0048] (1) Monomer preparation: Dissolve MAEA and AM in water at a molar ratio of 1:1.5 to prepare an aqueous solution with a total monomer concentration of 25%.
[0049] (2) Initiation system addition: Ammonium persulfate (0.5% of the total mass of monomers) and vitamin C (0.35% of the total mass of monomers) were added as the initiation system.
[0050] (3) Reaction process: Under nitrogen protection, the reaction was carried out at 65°C for 5 hours. After the reaction, the copolymer was precipitated with ethanol and dried to obtain the binary copolymer. The pH of the reaction system was controlled at 6.5. Dodecyl mercaptan (0.3% of the total mass of monomers) was added as a chain transfer agent.
[0051] (4) Preparation of grinding aid composition: The above-mentioned binary copolymer was prepared into a solution accounting for 30% of the total mass of the composition. Water was added to 50% of the total mass of the composition. Grinding aid enhancer (triisopropanolamine, accounting for 10% of the total mass of the composition) and retarder (citric acid, accounting for 1% of the total mass of the composition) were added. The mixture was stirred and mixed at 30°C for 0.7 hours to obtain a homogeneous solution.
[0052] Comparative Example 4 (AMPS / AM binary copolymer)
[0053] (1) Monomer formulation
[0054] 2-Acrylamide-2-methylpropanesulfonic acid (AMPS) and acrylamide (AM) were dissolved in water at a molar ratio of 0.4:1.5 to prepare an aqueous solution with a total monomer concentration of 25%.
[0055] (2) Triggering system integration
[0056] Ammonium persulfate (0.5% of the total monomer mass) and vitamin C (0.35% of the total monomer mass) were added as a redox initiation system.
[0057] (3) Reaction process
[0058] Under nitrogen protection, the reaction was carried out at 65°C for 5 hours; the pH of the reaction system was controlled at 6.5; dodecyl mercaptan (0.3% of the total mass of monomers) was added as a chain transfer agent; after the reaction was completed, the product was precipitated with ethanol and dried to obtain the AMPS / AM binary copolymer (weight average molecular weight of approximately 220,000).
[0059] (4) Formulation of grinding aid composition
[0060] The above-mentioned binary copolymer was prepared into a solution accounting for 30% of the total mass of the composition. Water was added to 50% of the total mass, and then the following were added: grinding aid: triisopropanolamine (accounting for 10% of the total mass of the composition); retarder: citric acid (accounting for 1% of the total mass of the composition). The mixture was stirred and mixed at 30°C for 0.7 hours to obtain a homogeneous solution.
[0061] Comparative Example 5 (MAEA / AMPS binary copolymer)
[0062] (1) Monomer formulation
[0063] Maleic ethanolamine ester (MAEA) and 2-acrylamide-2-methylpropanesulfonic acid (AMPS) were dissolved in water at a molar ratio of 1:0.4 to prepare an aqueous solution with a total monomer concentration of 25%.
[0064] (2) Triggering system integration
[0065] Ammonium persulfate (0.5% of the total monomer mass) and vitamin C (0.35% of the total monomer mass) were added as the initiation system.
[0066] (3) Reaction process
[0067] Under nitrogen protection, the reaction was carried out at 65°C for 5 hours; the pH of the reaction system was controlled at 6.5; mercaptoacetic acid (0.3% of the total mass of monomers) was added as a chain transfer agent; after the reaction was completed, the product was precipitated with ethanol and dried to obtain the MAEA / AMPS binary copolymer (weight average molecular weight of approximately 250,000).
[0068] (4) Formulation of grinding aid composition
[0069] The above-mentioned binary copolymer was prepared into a solution accounting for 30% of the total mass of the composition. Water was added to 50% of the total mass, and then the following were added: grinding aid: sodium gluconate (accounting for 10% of the total mass of the composition); retarder: tartaric acid (accounting for 1% of the total mass of the composition). The mixture was stirred at 30°C for 0.7 hours to obtain a homogeneous solution.
[0070] Performance testing:
[0071] 1. Grinding Energy Consumption Test Method
[0072] (1) Equipment
[0073] Ball mill: A laboratory ball mill equipped with an electrical energy monitoring device.
[0074] (2) Steps
[0075] Sample preparation: Take a certain amount of cement sample. Grinding aid addition: Add grinding aid according to the ratio. Grinding: Start the ball mill, set a fixed time, and record the power consumption. Calculation: Compare the energy consumption before and after adding the grinding aid, and calculate the reduction rate. Experimental results are shown in Table 1.
[0076] 2. Compressive strength test method
[0077] (1) Equipment
[0078] Curing chamber: Standard curing chamber. Testing machine: Compressive strength testing machine.
[0079] (2) Steps
[0080] Specimen preparation: Cement mortar specimens were prepared according to standard methods, with grinding aid added. Curing: Cured for 3 days under standard conditions. Testing: Compressive strength was tested using a testing machine. Calculation: The strength before and after adding the grinding aid was compared, and the improvement rate was calculated. The experimental results are shown in Table 1.
[0081] 3. Cement specific surface area test method
[0082] (1) Equipment
[0083] Surface area meter: Blaine surface area meter.
[0084] (2) Steps
[0085] Sample preparation: Dry the cement sample to constant weight and cool for later use. Filling: Fill the sample into a permeable cylinder and compact it. Testing: Conduct a permeability test according to standard methods and measure the specific surface area. The experimental results are shown in Table 1.
[0086] 4. Test method for grinding aid dosage
[0087] (1) Steps
[0088] Weighing: Weigh the cement and grinding aid using a balance. Calculation: Calculate the amount of grinding aid to be added according to the formula. The experimental results are shown in Table 1.
[0089] Table 1. Physicochemical properties characterization of grinding aids
[0090]
[0091] Data Analysis:
[0092] Compared with traditional grinding aids (Comparative Example 1), grinding energy consumption was reduced: the grinding energy consumption of Example 1 was reduced by 35%, while that of Comparative Example 1 was only reduced by 20%. This shows that the terpolymer significantly improves grinding efficiency and reduces energy consumption through adsorption and dispersion.
[0093] Improved 3-day compressive strength: The 3-day compressive strength of Example 1 increased by 32%, while that of Comparative Example 1 increased by only 15%. This indicates that the terpolymer can effectively promote the hydration reaction of cement and accelerate the early strength development.
[0094] Compared with the absence of chain transfer agent (Comparative Example 2), the grinding energy consumption was reduced: the grinding energy consumption of Example 1 was reduced by 35%, while that of Comparative Example 2 was only reduced by 28%. This indicates that the addition of chain transfer agent can effectively adjust the molecular weight and molecular weight distribution of the polymer, thereby improving the grinding aid effect.
[0095] Improved 3-day compressive strength: The 3-day compressive strength of Example 1 increased by 32%, while that of Comparative Example 2 increased by only 22%. This indicates that the addition of the chain transfer agent not only improves grinding efficiency but also promotes the early strength development of cement.
[0096] Chain transfer agents play a role in regulating the molecular weight and molecular weight distribution of polymers during polymerization. Without the addition of chain transfer agents, the molecular weight distribution of the polymer is relatively wide, leading to unstable performance of the grinding aid and resulting in inferior grinding aid effect and strength improvement compared to examples that incorporate chain transfer agents.
[0097] Compared with binary polymers (Comparative Examples 3, 4, 5), grinding energy consumption was reduced: Example 1 showed a 35% reduction in grinding energy consumption, while Comparative Examples 3, 4, and 5 only saw a 19-22% reduction. This indicates that the synergistic effect of the specific ratio of terpolymers (MAEA / AMPS / AM) can reduce energy consumption by 32%-38% in cement grinding. This effect stems from the following technical mechanism: the ethanolamine groups (-N(CHCHOH)) of maleic acid ethanolamine ester (MAEA) can react with the CaO on the surface of cement particles. 2 +、Al 3The formation of stable coordination bonds by metal ions effectively reduces the surface energy of particles, allowing mechanical energy to act more efficiently on particle crushing rather than being consumed by surface energy during the grinding process; the sulfonic acid group (-SOH) of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) ionizes into -SO3 in aqueous solution. - It imparts a strong negative charge to the surface of cement particles, preventing particle agglomeration through electrostatic repulsion and reducing the "secondary grinding" phenomenon during the grinding process; the nonionic properties of acrylamide (AM) bind to cement particles through hydrogen bonds, and its flexible long-chain structure forms a physical barrier on the particle surface, further preventing particle contact and agglomeration.
[0098] The terpolymer achieves optimal overall performance through the synergistic effect of MAEA adsorption-catalysis, AMPS electrostatic repulsion, and AM chain flexibility. The 3-day compressive strength is improved: the 3-day compressive strength of Example 1 increased by 32%, while that of Comparative Example 3 increased by only 25%. This indicates that the synergistic effect of the terpolymer not only improves grinding efficiency but also promotes the early strength development of cement.
[0099] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.
Claims
1. A composition of ultrafine cement grinding aid, characterized in that, Include: The composition comprises a terpolymer, accounting for 25% to 45% of the total mass of the composition; water, accounting for 45% to 55% of the total mass of the composition; and a grinding aid, accounting for 7% to 13% of the total mass of the composition, wherein the grinding aid is selected from at least one of triisopropanolamine, diethanolmonoisopropanolamine, and sodium gluconate.
2. The ultrafine cement grinding aid composition according to claim 1, characterized in that, It also contains 1% to 1.5% of a retarder, wherein the retarder is boric acid, citric acid or tartaric acid.
3. The ultrafine cement grinding aid composition according to claim 1, characterized in that, The terpolymer is prepared by free radical copolymerization of maleic ethanolamine ester, 2-acrylamide-2-methylpropanesulfonic acid and acrylamide, wherein the molar ratio of the monomers is 1:(0.3-0.6):(1.2-2.5), and the weight average molecular weight of the terpolymer is 200,000 to 350,000.
4. The ultrafine cement grinding aid composition according to claim 3, characterized in that, The preparation process of the terpolymer includes the following steps: (1) Dissolve maleic ethanolamine ester, 2-acrylamide-2-methylpropanesulfonic acid and acrylamide in water to prepare a monomer solution with a total monomer concentration of 22% to 28%; (2) Add an oxidation-reduction initiation system, wherein the initiation system contains ammonium persulfate and vitamin C, wherein the amount of ammonium persulfate added is 0.4% to 0.7% of the total mass of the monomers, the amount of vitamin C added is 0.3% to 0.4% of the total mass of the monomers, and add a chain transfer agent; (3) Under nitrogen protection, the reaction was carried out at 62-68°C for 4.5-5.5 hours. After the reaction was completed, the terpolymer was obtained by precipitation with ethanol and drying.
5. The ultrafine cement grinding aid composition according to claim 4, characterized in that, The pH of the reaction system in (3) is controlled at 6.2 to 6.
8.
6. The ultrafine cement grinding aid composition according to claim 4, characterized in that... , characterized in that, The chain transfer agent is also described as dodecyl mercaptan or thioglycolic acid, and the amount added is 0.2% to 0.4% of the monomer solution mass.
7. A method for preparing an ultrafine cement grinding aid composition according to any one of claims 1-6, characterized in that, Includes the following steps: The terpolymer was dissolved in water and stirred until completely dissolved; a grinding aid and a retarder were added sequentially, and the mixture was stirred and mixed at 28–35°C for 0.6–0.8 hours to obtain a homogeneous solution.
8. The application of the ultrafine cement grinding aid composition according to any one of claims 1-6 in the cement grinding process, characterized in that, The addition amount is 0.03% to 0.07% of the cement mass.
9. The application of the ultrafine cement grinding aid composition according to claim 8 in the cement grinding process, characterized in that, The cement has a specific surface area ≥ 550 m². 2 / kg of ultrafine cement.
10. The application of the ultrafine cement grinding aid composition according to claim 8 in the cement grinding process, characterized in that, The terpolymer or grinding aid composition can reduce grinding energy consumption by 32% to 38% and increase 3-day compressive strength by 28% to 35%.
Citation Information
Patent Citations
Copolymer macromolecular grinding assist dispersant and preparation method and application thereof
CN108409907A